Effect of Gender, Age, and Marital Status of Grocery Consumers on Their Perceived Retail Store Image : A Study of Organized Grocery Market in India - Parmod; Arora, Usha (Indian Journal of Marketing, 2021)
The retail industry is changing with an unprecedented pace. Specifically, in developing countries like India, this change is disrupting the landscape of the retail sector with an intensity never seen before. To get an edge over competitors and to perform in a better way, it will be critical for retailers to understand the retail store attributes which attract the consumers and keep them coming back. To obtain a comprehensive understanding of grocery consumers’ perceived retail store image across various demographic groups in context of India was the basic purpose of this paper. For this, a survey of grocery consumers, who visited organized grocery stores to purchase groceries at least once in a month, was conducted. Initially, 500 consumers were approached to fill a standardized questionnaire, and 469 questionnaires complete in all manners were used for the final analysis. The factor analysis resulted in nine major dimensions of store image construct. Furthermore, with the help of ANOVA and t - statistics, it was tested if the demographic factors like age, gender, and marital status significantly affected the perceived store image of grocery consumers. In this study, significant differences emerged in consumers’ perception of store image dimensions based on age and marital status. In case of gender, no significant difference was observed on any store image dimension. The findings of this study would lead to an improved understanding of the linkage between grocery consumers’ demographic attributes and their perceived level of store image in the context of a developing country.